Yes we can! The Raffles Dialogue on Human Wellbeing and Security - Dr. Tikki Pang; Yap Seng Chong; Hildy Fong; Eva Harris; Richard Horton; Kelley Lee; Eugene Liu; Kishore Mahbubani; Mari Pangestu; Khay Guan Yeoh; John Eu-Li Wong (The Lancet Global Health, 2015)
The future of human wellbeing and security depends on our ability to deal with the multiple effects of globalisation and on adoption of a new paradigm and philosophy for living and for health that emphasises people's wellbeing and social justice. Such was the topic of the inaugural Raffles Dialogue on Human Wellbeing and Security held in Singapore on Feb 2–3, 2015. Participants agreed that, to achieve these goals, four conditions must be met. First, equity must be integral to the implementation of technology. Second, there is an urgent need for innovations within our global institutions to make them “fit for purpose” in a rapidly changing world. Third, we must find the right balance between the roles of government and markets so that all those in need can access affordable medicine and health care. Finally, we must realise that we live in a small and interdependent “global village”, where Asian countries need to assume greater leadership of our global village councils. This is the great imperative of our times.